2014
DOI: 10.1007/s11604-014-0333-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of a breast density measurement within a direct photon-counting mammography scanner system

Abstract: The calculated volumetric glandularity using this new application should correspond well with the true volumetric density of each breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Breast density has been established as an independent risk factor for breast cancer. The high reproducibility and accuracy of volumetric breast density (VBD) evaluation techniques from mammographic images have been reported in several studies (Skippage et al 2013 ; Wang et al 2013 ; Hammann-Kloss et al 2014 ; Machida et al 2014 ). Additionally, studies have confirmed a strong correlation between VBD, calculated from mammography, and breast cancer risk (Eng et al 2014 ; Brand et al 2014 ; Trinh et al 2015 ; Schetter et al 2014 ).…”
Section: Introductionmentioning
confidence: 93%
“…Breast density has been established as an independent risk factor for breast cancer. The high reproducibility and accuracy of volumetric breast density (VBD) evaluation techniques from mammographic images have been reported in several studies (Skippage et al 2013 ; Wang et al 2013 ; Hammann-Kloss et al 2014 ; Machida et al 2014 ). Additionally, studies have confirmed a strong correlation between VBD, calculated from mammography, and breast cancer risk (Eng et al 2014 ; Brand et al 2014 ; Trinh et al 2015 ; Schetter et al 2014 ).…”
Section: Introductionmentioning
confidence: 93%
“…The Philips Spectral Density Measurement Tool outputs VBD, total fibroglandular volume and total breast volume as well as a “MicroDose Density Score”, analogous to a BI-RADS categorization [65]. However, clinical studies using this method have been small and limited [66,67,68]. …”
Section: Fully-automated Density Assessmentmentioning
confidence: 99%
“…A direct photon-counting mammography scanner system is able to acquire spectral energy data of incident photon particles of each mammogram without additional radiation or risk of misregistration, and proportions of dense tissue within breasts are calculated out of acquired spectral energy data. Machida et al [43] previously assessed the clinical feasibility of an application within a mammography system using a photon-counting technology, which calculates volumetric glandularity (proportion of fibroglandular tissue within a breast), and showed a high accuracy using this technology.…”
Section: Measuring Breast Composition Using Photoncounting Technologymentioning
confidence: 99%